Relation between width of zero-bias anomaly and Kondo temperature in transport measurements through correlated quantum dots: Effect of asymmetric coupling to the leads - Perez Daroca, Diego Raul (2018)
The zero-bias anomaly at low temperatures, originated by the Kondo effect when an electric current flows through a system formed by a spin-1/2 quantum dot and two metallic contacts is theoretically investigated. In particular, we compare the width of this anomaly 2TNE with that of the Kondo resonance in the spectral density of states 2TKρ, obtained from a Fano fit of the corresponding curves and also with the Kondo temperature TKG defined from the temperature evolution of the equilibrium conductance G(T). In contrast to TKG and 2TKρ, we found that the scale 2TNE strongly depends on the asymmetry between the couplings of the quantum dot to the leads while the total hybridization is kept constant. While the three scales are of the same order of magnitude, 2TNE and TKρ agree only in the case of large asymmetry between the different tunneling couplings of the contacts and the quantum dot. On the other hand, for similar couplings, TNE becomes larger than TKρ, reaching the maximum deviation, of the order of 30%, for identical couplings. The fact that an additional parameter to TNE is needed to characterize the Kondo effect, weakening the universality properties, points that some caution should be taken in the usual identification in experiments of the low temperature width of the zero-bias anomaly with the Kondo scale. Furthermore, our results indicate that the ratios TNE/TKG and TKρ/TKG depend on the range used for the fitting.